TRADISI PERNIKAHAN DI DEPAN MAYIT ATAS DASAR WASIAT DALAM PERSPEKTIF HUKUM ISLAM - Zakiatus Safira; Ibnu Jazari; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Regarding the issue of marriage, of course, people always have their own customs or traditions. One of them is the tradition of marriage in front of the deceased, which is a traditional tradition of marriage that is only done in certain areas. As has been explained that the contract at this marriage is carried out near the body of one of the parents of the prospective bride and groom. As a form of final respect to parents. However, there is a lot of controversy over this tradition. With the contradiction in the implementation of the marriage in front of the deceased, presumably this tradition needs to be reexamined using principles so that the tradition can be categorized as a valid custom and its truth can be preserved, besides that it can become a reference for legal considerations and customs of the fasid that must be eliminated because its freedoms. Questions like that will be discussed in this study. This study uses the library method by utilizing library sources to obtain research data. The results of this study conclude that from the perspective of traditional Islamic law such as this is permissible, there is no deviation from this tradition while still stipulating the conditions that apply to marriage. And more importantly, because there are different traditions that are believed by some people because not all can accept the various traditions that exist in their respective circles. So it is better to respect each other for the tradition of marriage in front of the deceased and hopefully it will be of benefit to all of us. Keywords: tradition, wedding in front of mayit, testament, Islamic law